Methylglyoxal binds to amines in honey matrix and 2′-methoxyacetophenone is released in gaseous form into the headspace on the heating of manuka honey. (1st February 2021) - Kato, Yoji; Kishi, Yui; Okano, Yayako; Kawai, Masaki; Shimizu, Michiyo; Suga, Naoko; Yakemoto, Chisato; Kato, Mai; Nagata, Akika; Miyoshi, Noriyuki
Highlights: Changes in nine chemicals in manuka honey by thermal treatments were analyzed. Methylglyoxal (MGO) and 2′-methoxyacetophenone (MAP) were lost by high heating. MGO was lost by generation of adducts with l -proline, lysine, and arginine residues. MAP was released in the gaseous form into the headspace on heating. Abstract: Reports on the thermal stability of manuka honey in terms of food processing have been few. This study investigated changes in nine characteristic chemicals of manuka honey during heating. Among these, methylglyoxal (MGO) and 2′-methoxyacetophenone (MAP) were significantly decreased by heating at 90 °C. To elucidate the mechanism for this decrease, artificial honey was prepared from sugars and water with MAP or MGO and then heated. The decrease of MGO was enhanced with l -proline, lysine, or arginine derivatives, accompanied by formation of 2-acetyl-1-pyrroline, MGO-derived lysine dimer, or argpyrimidine, respectively, suggesting that an amino–carbonyl reaction is one pathway for the loss of MGO. The decrease of MAP in the artificial honey depended on the volume of headspace in a vessel. MAP from heated manuka honey was also detected in the gas phase, indicating that MAP was vaporized. Heating could thus reduce the beneficial and/or signature molecules in honey.